An Examination of Adherence to Infection Prevention Protocols among Nurses and Laboratory Technicians in Medical Clinics - Alaldbey, Hussain Hadi Ali; ALaskar, Mohsen Mohammed Yahya; ALyami, Hussein Saleh Ali; Al khamsan, Hamad Mohammed Yahya; ALsenan, Hassan Masud Mane (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
This article critically examines the adherence levels of nurses and laboratory technicians to infection prevention protocols in medical clinics, a crucial factor in ensuring patient safety and reducing healthcare-associated infections (HAIs). Despite the established protocols and guidelines, there is a variable adherence among healthcare workers, which significantly impacts the effectiveness of infection control measures. This comprehensive review explores the current adherence status, identifies existing challenges, and discusses the implications of non-compliance on patient outcomes and healthcare systems. Utilizing a mix of current literature, case studies, and expert interviews, the article highlights the importance of rigorous adherence to infection control practices and delves into strategies for improving compliance, including enhanced training, technological advancements, and policy implementation. The discussion extends to the ethical and legal considerations, emphasizing the responsibility of healthcare professionals in preventing HAIs. The aim is to provide a nuanced understanding of the factors influencing adherence to infection prevention protocols and to suggest actionable steps for healthcare facilities to improve safety standards.